What are Charities Doing?: A Content Analysis of Charity Print Media - Ridge, Kiera (2008)
The importance of charitable organisations can be seen through the huge role they play in our society. However, many of them are suffering from diminishing donations and a pool of aging donors. There is a growing need for a greater understanding of what marketing communications techniques charities are using and how these techniques can be improved. This research will fill the gap in the knowledge base concerning which techniques marketing charities are currently using by presenting a content analysis of advertising print media. As this sort of research has not been done before guidance will be taken from other industry examples, such as Pollay (1983). The results show a lack of consistency between industry advice of targeting regular donations and the content of the advertisements which are mainly targeting one-off donations and that the majority of charity advertisements are currently using positive appeals and a collective perspective. The results were analysed using chi-squared tests and found a statistically significant relationship between the type of perspective portrayed in the advertisement and both type of request and type of appeal. The author advises that in the current donor climate more emphasis should be placed on investigating the effectiveness of those marketing techniques found to be most frequently being used by charities.